Pemodelan dan Evaluasi Proses Bisnis Pengembangan Perangkat Lunak dengan menerapkan Metode Process Mining dan Quality Evaluation Framework (QEF) Studi pada PT. XYZ - Nafiani Nafiani; Yusi Tyroni Mursityo; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
XYZ is a company that sells services and solutions to customer problems, services and solutions sold are products that have been developed previously by PT. XYZ and will continue to be developed to adjust the addition of functions according to customer demand. To be able to achieve the vision and mission of an organization, PT. XYZ must have a good software development business process. Currently, the service and solution development process still not have a written Standard OperationaI Procedure (SOP) that can be the problem in evaluating system performance and the passing of a product from a predetermined time limit. Therefore, we need to carry out further evaluations so as not to have a negative impact on the product development process. EvaIuation is done by using interview sources and event logs that use process mining methods to further process and analyze event logs with the help of Disco and ProM 6 Tools. After that, the evacuation process will be continued by using the Quality Evaluation Framework (QEF) to compare the target values with the interview results and event log values. The evaluation results have 13 quality factors were concerned, 4 quality factors including those that were not in line with the company's target because the processing time recorded in the event log exceeded the target. The activities listed in the event log are not procedurally appropriate, such as processes that were not closed for a long time and processes that have the same start and finish time.